THE END OF POSTCOMMUNISM AND THE TRENDS OF THE FURTHER DEVELOPMENT OF EX-POSTCOMMUNIST COUNTRIES - RomanyukО. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2021)
The article is devoted to clarifying the problem of the end of postcommunist transformations and the essence of the further development of the ex-postcommunist countries. The avalanche collapse of the communist regimes at the turn of the 1980s and 1990s led to the beginning of postcommunist transformations. Today it can be stated that this process is over. The author argues this conclusion with the following considerations: 1) any transformational process, the essence of which is to replace one quality of society or its political system with another, cannot go on indefinitely, it must end someday; 2) the end of the transformation process is due to the establishment of a new quality; 3) the totalitarian nature of the previous communist regimes presupposes the multivariate end of postcommunist transformations. Various postcommunist countries have achieved different results during transformations. In Central-Eastern Europe, the Baltic States, and a number of countries in South-Eastern Europe, postcommunist transformations have culminated in the establishment of democracy. The transformations of Azerbaijan, Kazakhstan, Tajikistan and Uzbekistan was over the establishment of authoritarian regimes. Neo-totalitarian regimes have emerged in Belarus, Russia, and Turkmenistan. In Albania, Bosnia and Herzegovina, Armenia, Georgia, Kosovo, Macedonia, Moldova and Ukraine, political development fluctuates between democracy and authoritarianism for a long time. The author concludes that the period of postcommunism in all these countries finally over in the middle of 2010s. The end of postcommunism marked the beginning of a new stage in the socio-political development of the ex-communist countries. Its main tendencies are revealed in this paper. The author includes in such: 1) a fall the level of democracy in Central-Eastern and South-Eastern Europe; 2) a strengthening differentiation of political development of single regions and the countries; 3) a growth of nationalism; 4) a changes in relations with the EU; 4) a strengthening Russia’s interference.